The influence of the six domains of entrepreneurial ecosystem on the Malaysian small and medium enterprises performance - Abdullah, Ammar Harith (2018)
The government of Malaysia has ensured Small, Medium Enterprises (SMEs) Entrepreneurial Ecosystem is able to increase entrepreneurial activities. Blueprints such as the Malaysian SME Masterplan 2012-2020 are among the notable efforts to aid the development, sustainability, and growth of SMEs. However, the SMEs are still entangled with issues and challenges which is reflected in the high failure rate, close to 60 percent and on a constant rise. Therefore, this study focuses on exploring and examining the SME Entrepreneurial Ecosystem to present a framework and to examine the influence of the domains of the Entrepreneurial Ecosystem on the SME Performance. Mixed-method research design was employed. For qualitative method, a total of 131 entrepreneurs were interviewed, and for quantitative design a total of 877 entrepreneurs were surveyed. The qualitative finding resulted in a detailed framework with the discovery of a new domain called Entrepreneurial Networking, and 6 other domains with 23 sub-categories respectively. The quantitative finding indicated the ecosystem is positively correlated to performance, with Pearson correlation coefficient of r = 0.682. And the other variables indicated r = 0.593 (Policy), r = 0.475 (Finance), r = 0.550 (Culture), r = 0.556 (Support), r = 0.651 (Human Capital) and r = 0.572 (Market). Human capital (0.651) was identified to have a strong positive correlation towards the performance. Furthermore, multiple regression analysis indicated that the model explained 51% of the variance (R2 = 0.509, F (6.870) = 150.373, p < 0.001). Human Capital had strongest (β = 0.345, p< .001). Hence, the study revealed that the domains have substantial contribution to the success of SMEs. This study discovered the framework for Malaysian entrepreneurial ecosystem, discovered a new domain, and its influence on performance.